The formation of the competence educate in the conservation of phytodiversity in the career degree in Biology Education - Chibás Creagh, Mario; Méndez Santos, Isidro Eduardo; Piclín Minot, Jesús (Transformación, 2025)
Introduction: Environmental degradation and an unsustainable economic model require universities to value the role of biology teachers in their ability to contribute to reversing the loss of biodiversity and achieving sustainable development. Objective: The research argues a pedagogical model of environmental education oriented to the formation of the competence educate in the conservation of phytodiversity in the Bachelor’s Degree in Biology Education. Methods: Historical-logical methods, induction-deduction, analysis-synthesis, bibliographic review, documentary analysis, as well as systemic-structural-functional and modeling were used. Result: The fundamental contribution is the design of the training model of the competence educate in the conservation of phytodiversity, which includes the basis for the integration of knowledge, the axiological-developmental articulation, and the performance with suitability to educate in the conservation of phytodiversity. Conclusion: The modeling of the formation of the competence educate in the conservation of phytodiversity establishes a synergy between the three processes that describe its components and fundamental qualities, which respectively allude to the integrated apprehension of knowledge and suitability to educate in the conservation of phytodiversity, as well as perfective education in the conservation of phytodiversity. From all this emerges a higher order: the professionalization of the teacher in training to educate in the conservation of phytodiversity.